III Conference la ValSe-Food and VI Symposium Chia-Link Network - Haros, Claudia; Muñoz, Loreto (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The seeds and fruits (or their parts) of IberoAmerican crops have high nutritional and functional properties that could be utilized in a wide range of foods. The crops included in this book are amaranth (Amaranthus spp.), quinoa (Chenopodium quinoa), kañiwa (Chenopodium pallidicaule), chia (Salvia hispanica L.), Andean maize (Zea mays L.), moringa (Moringa oleifera), broad beans (Vicia faba L.), kurugua (Sicana odorifera), sacha inchi (Plukenetia huayllabambana), and tarwi (Lupinus mutabilis), all of which are still underutilized. Their cultivation is low; nevertheless, in recent years, worldwide demand of some of them has increased immensely, resulting in an increase in their production. Ancient IberoAmerican crops have been widely recognized for their nutritional value by food scientists and food producers because they contain high-quality proteins, large quantities of micronutrients such as minerals and vitamins, and bioactive compounds. Moreover, they are gluten-free, which makes them suitable for people suffering from various gluten intolerances. This book summarizes the large amount of investigations in this field in the recent years and provides knowledge of all the relevant areas of food science. The editors hope that this book will contribute to their increased use in human nutrition by consumers worldwide.